Perubahan harmoni wajah pasca perawatan kelas II skeletal dengan pencabutan dua premolar satu atas menurut analisis Arnett dan BergmanChanges in facial harmony after skeletal class II treatment with extraction of two maxillary first premolars based on Arnett and Bergman analysis - Muslim Yusuf; Nurhayati Harahap; Dhita Kartika Nasution (Padjadjaran Journal of Dental Researchers and Students, 2021)
Pendahuluan: Arnett dan Bergman (1999) membuktikan bahwa perawatan ortodonti, analisis jaringan lunak wajah, diagnosis dan rencana perawatan memiliki parameter nilai harmoni sebagai kunci penetapan estetika wajah. Perawatan maloklusi klas II skeletal disertai proganotisme maksilaris umumnya dilakukan dengan pencabutan dua premolar satu atas untuk mengkoreksi profil wajah pasien. Tujuan penelitian untuk menganalisis perubahan nilai harmoni wajah pasca perawatan maloklusi kelas II dengan pencabutan premolar satu atas menurut analisa Arnett dan Bergman. Metode: Jenis penelitian analitik observasional dengan teknik pengambilan sampel purposive sampling. Sampel penelitian 72 foto sefalometri lateral maloklusi kelas II skeletal sebelum dan setelah perawatan ortodonti. Penilaian harmoni jaringan lunak dibagi menjadi 4, yaitu harmoni intramandibular, harmoni antar rahang, orbita ke rahang dan keseimbangan wajah. Data menggunakan Shapiro Wilk menunjukkan tidak berdistribusi normal. Uji yang digunakan Shapiro Wilk dan  analisis Spearman. Hasil: Terdapat perubahan harmoni intramandibular dan keseimbangan wajah pada maloklusi kelas II skeletal dengan pencabutan premolar satu atas sebelum dan setelah perawatan (p=0,025;p=0,032). Tidak terdapat perubahan nilai harmoni antar rahang dan orbita ke rahang pada maloklusi kelas II skeletal dengan pencabutan premolar satu atas sebelum dan setelah perawatan. Ada pengaruh besar retraksi gigi insisivus terhadap nilai harmoni wajah sebelum dan setelah perawatan pada perawatan kelas II dengan pencabutan dua premolar atas (p= 0.001). Simpulan: Perawatan maloklusi kelas II skeletal dengan pencabutan dua premolar satu atas  memiliki hubungan antara besar retraksi dengan perubahan nilai harmoni wajah berdasarkan analisa Arnett dan Bergmann. Kata kunci: Maloklusi kelas II skeletal, pencabutan dua premolar pertama atas, nilai harmoni wajah. ABSTRACT Introduction: Arnett and Bergman (1999) have proved that orthodontic treatment, facial soft tissue analysis, diagnosis, and treatment plan have parameters of harmony values as the key to determining facial aesthetics. Treatment of skeletal class II malocclusion with maxillary prognathism is generally performed by extracting two maxillary first premolars to correct the patient’s facial profile. This study was aimed to analyse changes in the facial harmony values after class II malocclusion treatment with the extraction of the maxillary first premolar following Arnett and Bergman’s analysis. Methods: This research was observational analytic with a purposive sampling technique. The study sample was 72 images of skeletal class II malocclusion lateral cephalometry before and after orthodontic treatment. Assessment of soft tissue harmony was divided into four, namely intramandibular harmony, intermaxillary harmony, orbital to jaw harmony, and facial balance. Data was not normally distributed, as resulted from Shapiro Wilk analysis. The analysis in this study was conducted using Shapiro Wilk and Spearman’s analysis. Results: There were changes in intramandibular harmony and facial balance in skeletal class II malocclusion with the maxillary first premolar extraction before and after treatment (p=0.025 and p=0.032, respectively ). There was no change found in the value of intermaxillary harmony and the orbital to the jaw harmony in skeletal class II malocclusion with extraction of the maxillary first premolar before and after treatment. There was a high effect of incisor retraction on the facial harmony values before and after treatment in class II treatment with extraction of two maxillary premolars (p=0.001). Conclusion: Treatment of skeletal class II malocclusion with extraction of two maxillary first premolars has a relationship between the magnitude of retraction and changes in facial harmony values based on Arnett and Bergmann’s analysis.Keywords: Class II skeletal malocclusion, extraction of two maxillary first premolar, facial harmony.